2021
DOI: 10.1177/1932202x211018646
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Advanced Placement to Improve College Outcomes and Narrow Racial/Ethnic and Socioeconomic Disparities

Abstract: The U.S. economy requires a highly educated workforce, yet too few black, Latino, and low-income students attend, persist, and graduate from college. The present study examines the college outcomes of participants in a model Advanced Placement® (AP) intervention to shed light on its effectiveness and determine whether improving AP participation and performance is a promising strategy for closing persistent racial/ethnic and socioeconomic disparities in college outcomes. Findings suggest the college outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Also compared were the results of their initial database, which was described above, to the results for the Massachusetts's students who graduated in the 2010-2011 school year. College outcomes for students who participated in the Advanced Placement STEM & English program were better than the college outcomes for all students in the State of Massachusetts (Phillips & Lane, 2021). Regarding Black, Hispanic, and students who were economically disadvantaged, students who had participated in the Advanced Placement STEM & English program were 18.37 to 29.56 percentage points higher in rates of college matriculation, persistence, and graduation than the Massachusetts students with similar racial and economic factors (Phillips & Lane, 2021).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Also compared were the results of their initial database, which was described above, to the results for the Massachusetts's students who graduated in the 2010-2011 school year. College outcomes for students who participated in the Advanced Placement STEM & English program were better than the college outcomes for all students in the State of Massachusetts (Phillips & Lane, 2021). Regarding Black, Hispanic, and students who were economically disadvantaged, students who had participated in the Advanced Placement STEM & English program were 18.37 to 29.56 percentage points higher in rates of college matriculation, persistence, and graduation than the Massachusetts students with similar racial and economic factors (Phillips & Lane, 2021).…”
Section: Introductionmentioning
confidence: 82%
“…In another study, Phillips and Lane (2021) investigated college outcomes for 11,190 students who had participated in an Advanced Placement exam and graduated from a high school, between the 2008-2009 and 2012-2013 school years. Asian, White, and students who were not economically disadvantaged had better college matriculation and persistence rates than Black, Hispanic, and students who were economically disadvantaged (Phillips & Lane, 2021). Also compared were the results of their initial database, which was described above, to the results for the Massachusetts's students who graduated in the 2010-2011 school year.…”
Section: Introductionmentioning
confidence: 99%
“…Jackson (2012) indicates that this result is more likely due to the comprehensive implementation of all NMSI program components at targeted high schools, rather than any individual component, which included aggressive recruitment to AP MSE courses, teacher PD, teacher and student supports, and incentive awards. Phillips and Lane (2021) found that participants in a similar program in Massachusetts had better college outcomes than similar non-participants, and that participation and success in the program were significantly associated with positive college outcomes. Fischer et al (2020) investigated school, teacher, teaching practice, and PD "levers" that may improve student performance on AP science exams.…”
Section: College Readiness Programsmentioning
confidence: 94%
“…Its focus on STEM (science, technology, engineering, mathematics) areas addresses a perceived shortfall in achievement by American students, who lag behind students from many industrialized nations (National Center for Educational Statistics, 2013), though some believe this shortfall is misleading (e.g., Carnoy & Rothstein, 2013). Attention to AP math, science and English (MSE) courses is supported by research showing positive impacts of AP qualifying scores on college outcomes, particularly for underrepresented minority students (Phillips & Lane, 2021). The funded proposal enabled AP-TIP IN to implement NMSI's college-readiness program in Indiana from 2012 through 2017, including a holistic implementation of key interventions:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation